2002
DOI: 10.1152/ajpheart.00919.2001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-monocyte chemoattractant protein-1 gene therapy attenuates pulmonary hypertension in rats

Abstract: Monocyte/macrophage chemoattractant protein-1 (MCP-1), a potent chemoattractant chemokine and an activator for mononuclear cells, may play a role in the initiation and/or progression of pulmonary hypertension (PH). To determine whether blockade of a systemic MCP-1 signal pathway in vivo may prevent PH, we intramuscularly transduced a naked plasmid encoding a 7-NH(2) terminus-deleted dominant negative inhibitor of the MCP-1 (7ND MCP-1) gene in monocrotaline-induced PH. We also simultaneously gave a duplicate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 25 publications
4
76
1
1
Order By: Relevance
“…The CCL3 and CCL4 genes that code for monocyte/macrophage chemoattractant protein-1 alpha and beta (MCP-1a and MCP-1b), respectively, are of particular interest. Inhibition of these genes has been shown to prevent monocrotaline-induced pulmonary hypertension, suggesting a role for this chemokine in the pathogenesis of pulmonary vascular remodeling (32).…”
Section: Discussionmentioning
confidence: 99%
“…The CCL3 and CCL4 genes that code for monocyte/macrophage chemoattractant protein-1 alpha and beta (MCP-1a and MCP-1b), respectively, are of particular interest. Inhibition of these genes has been shown to prevent monocrotaline-induced pulmonary hypertension, suggesting a role for this chemokine in the pathogenesis of pulmonary vascular remodeling (32).…”
Section: Discussionmentioning
confidence: 99%
“…Adult male Sprague-Dawley rats (Charles River, Yokohama, Japan; 250 to 300 g body weight) were injected subcutaneously with 60 mg/kg MCT (Wako), which induces severe PAH in 3 weeks. 12,17 In a prevention protocol, animals were divided into 4 groups that received intratracheal instillation of phosphate-buffered saline (PBS), pitavastatin only (100 g), FITC-NP (1 mg PLGA), or pitavastatin-NP (100 g pitavastatin per mg PLGA) immediately after MCT injection. For intratracheal instillation, a 0.1-mL suspension of pitavastatin, FITC-NP, or pitavastatin-NP was injected gently into the trachea of animals, accompanied by an equal volume of air.…”
Section: Experimental Animal Modelsmentioning
confidence: 99%
“…RV systolic pressure and systemic blood pressure were measured with a polygraph system (AP-601G, Nihon Kohden). 12,17 Echocardiographic Measurements of RV and PA Hemodynamics…”
Section: Direct Rv Pressure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies have also shown that MCP-1 plays a role in monocrotaline-induced media hypertrophy. 29 Apparently, in the described flow-associated PAH model, MCP-1 is also activated by other factors than Egr-1. Interestingly though, perivascular macrophage infiltration, a known result of MCP-1 activation, was threefold higher after increased pulmonary blood flow (MϩF 30 versus M 30) and seen to be located around neointimal lesions.…”
Section: Egr-1 Transcription During Pulmonary Vascular Remodelingmentioning
confidence: 91%